Web-Based Instructional Wrappers for Immersive Technology: A Gagne-Based Google Sites Design to Mitigate Cognitive Load and Enhance Science Literacy - Dina Fajrin; Laifa Rahmawati; Aghea Tahta Wahyu Azizah (Assyfa Learning Journal, 2026)
The low level of scientific literacy and weak scientific communication skills among Indonesian students present critical challenges due to cognitive overloads in abstract learning. This study aims to evaluate the effect of an Augmented Reality (AR) ecosystem integrated within a structured Google Sites instructional wrapper—designed systematically using Gagne’s Nine Events of Instruction—on junior high school students' scientific literacy and scientific communication skills. Utilizing a quasi-experimental design with a Non-equivalent Control Group model, this study involved an experimental group (n = 24) learning with the Gagne-structured Web-AR Google Sites and a control group (n = 22) utilizing PowerPoint-integrated Project-Based Learning. Instrument reliability was confirmed via Borich’s Percentage of Agreement (100%), while hypotheses were tested using Paired Samples T-Test and Normalized Gain (N-Gain) analysis. The results revealed a highly significant improvement in scientific literacy within the experimental group (t = -15.461; p = 0.000; mean difference = 35.33 points), outperforming the control group's posttest average (74.29 vs 62.41). Furthermore, the experimental group achieved significantly higher scientific communication skills (t = 5.520; p = 0.000). The N-Gain analysis confirmed that the instructional wrapper approach achieved higher effectiveness (0.62; medium-approaching-high) than the control model (0.45). In conclusion, anchoring immersive AR technologies within a structured web-based instructional wrapper effectively minimizes technological barriers and extraneous cognitive load, seamlessly accelerating students' multidimensional science competencies.